Chemopreventive and Antitumor Efficacy of Curcumin in a Spontaneously Developing Hen Ovarian Cancer Model - Şahin, Kazım; Orhan, Cemal; Tuzcu, Mehmet; Şahin, Nurhan; Tastan, Hakki; Ozercan, Ibrahim Hanifi; Ozpolat, Bulent (Amer Assoc Cancer Research, 2018)
We investigated the effect of daily dietary curcumin intake on the development and progression of spontaneous ovarian cancer in a galline (hen) model, as the chicken is the only nonhuman animal in which ovarian cancer spontaneously develops with a high prevalence. At the end of 12 months, ovarian cancer had spontaneously developed in 39% (35/90) of control hens not fed curcumin (n = 90). In comparison, it spontaneously developed in 27% (24/90) and 17% (15/90) of hens given curcumin at 25.8 (n = 90) and 53.0 mg/day (n = 90), respectively (P = 0.004). This represented significant dose-dependent reductions in overall ovarian cancer incidence in the 25.8 and 53.0 mg/day curcumin-fed groups (31% and 57%, respectively). Daily curcumin intake also reduced ovarian tumor sizes (P = 0.04) and number of tumors (P = 0.006). Evaluation of the molecular mechanisms underlying the che-mopreventive and antitumor effects of curcumin revealed that NF-kappa B and STAT3 signaling pathways were significantly inhibited but that the nuclear factor erythroid 2/heme oxygenase 1 antioxidant pathway was induced by curcumin intake in a dose-dependent manner in ovarian tissues (P < 0.05). Sequencing of the Ras family genes (KRAS, NRAS, and HRAS) revealed less frequent KRAS and HRAS mutations in ovarian tumors in the curcumin-fed animals. In conclusion, our results demonstrated for the first time that daily curcumin intake leads to a significant and dose-dependent reduction in spontaneous ovarian cancer incidence and tumor growth, indicating a tremendous role for curcumin as a chemopreventive strategy for ovarian cancer. (C) 2017 AACR.
Keywords: Nf-Kappa-B; Familial Adenomatous Polyposis; Clinical-Trial; Laying Hens; Prevention; Expression; Strategy; Pathway; Adenocarcinomas; Angiogenesis